Pendidikan Budi Pekerti Dalam Sastra: Menyibak Budaya Tata Krama Dalam Novel-Novel Etnografis - Herman Didipu (Universitas Negeri Surabaya, 2018)
This study aims to describe the culture of manners in ethnographic novels. The method used in this research is decriptive qualitative. Research data sourced from three ethnographic novels, namely Namaku Teweraut by Ani Sekarningsih (2000), Manusia Langit by J.A. Sonjaya (2010), and Cinta Putih di Bumi Papua by Dzikry El Han (2014). Data were collected by using close reading technique and noting technique. The collected data were then analyzed in Miles and Huberman's three stages of qualitative data analysis, i.e. data reduction, data display, and conclusion. The results of the study show that the culture of manners embodied in ethnographic novels are respecting parents, respecting customary stakeholder decisions, respecting guests, greeting and introducing oneself, and ethic of speech.Keywords: character, cultural value, manners, ethnographic novels.